Social Brand Dynamics in Green Marketing Literacy - Sudirjo, Frans; Nailul, Muhammad (Westscience Press, 2025)
This study explores the evolving relationship between social brand dynamics and green marketing literacy through a comprehensive bibliometric analysis. Drawing on data from the Scopus database and visualized using VOSviewer, the research maps the intellectual structure, thematic clusters, temporal trends, and global collaboration networks within the field. The co-occurrence analysis reveals that core concepts such as green marketing, sustainability, and corporate social responsibility are central to the discourse, while recent attention has shifted toward social media, brand image, and trust-building strategies. Temporal mapping indicates a growing interest in digital engagement and participatory branding, suggesting that green marketing literacy is increasingly shaped by consumer interaction within online ecosystems. The author co-citation network highlights both foundational contributors and emerging thought leaders, while country collaboration mapping reflects a globalizing research agenda led by the United States, India, and China. The findings underscore the interdisciplinary and socially constructed nature of green marketing literacy and call for future research to examine the digital, behavioral, and contextual factors that influence consumer understanding and trust in green branding practices.